Experimental lupus is aggravated in mouse strains with impaired induction of neutrophil extracellular traps - Kienhofer, Deborah; Hahn, Jonas; Stoof, Julia; Csepregi, Janka Zsofia; Reinwald, Christiane; Urbonaviciute, Vilma; Johnsson, Caroline; Maueröder, Christian; Podolska, Malgorzata; Biermann, Mona; Leppkes, Moritz; Harrer, Thomas; et al. (JCI Insight, 2017)
Many effector mechanisms of neutrophils have been implicated in the pathogenesis of systemic lupus erythematosus (SLE). Neutrophil extracellular traps (NETs) have been assigned a particularly detrimental role. Here we investigated the functional impact of neutrophils and NETs on a mouse model of lupus triggered by intraperitoneal injection of the cell death-inducing alkane pristane. Pristane-induced lupus (PIL) was aggravated in 2 mouse strains with impaired induction of NET formation, i.e., NOX2-deficient (Ncf1-mutated) and peptidyl arginine deiminase 4-deficient (PAD4-deficient) mice, as seen from elevated levels of antinuclear autoantibodies (ANAs) and exacerbated glomerulonephritis. We observed a dramatically reduced ability to form pristane-induced NETs in vivo in both Ncf1-mutated and PAD4-deficient mice, accompanied by higher levels of inflammatory mediators in the peritoneum. Similarly, neutropenic Mcl-1ΔMyelo mice exhibited higher levels of ANAs, which indicates a regulatory function in lupus of NETs and neutrophils. Blood neutrophils from Ncf1-mutated and human individuals with SLE exhibited exuberant spontaneous NET formation. Treatment with specific chemical NOX2 activators induced NET formation and ameliorated PIL. Our findings suggest that aberrant NET is one of the factors promoting experimental lupus-like autoimmunity by uncontrolled release of inflammatory mediators.
EVALuna2:1833